2021
DOI: 10.1136/bmjdrc-2021-002134
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and cardiometabolic health in adolescents with type 2 diabetes: a cross-sectional study

Abstract: IntroductionYouth living with type 2 diabetes display increased risk of cardiovascular disease (CVD). It is unclear if regular physical activity (PA) modifies this risk.Research design and methodsWe compared CVD risk factors in a cross-sectional study of 164 youth with type 2 diabetes stratified according to weekly vigorous-intensity PA. Outcomes were hemoglobin A1c (HbA1c), ambulatory blood pressure (BP; ambulatory 24-hour readings), plasma lipoproteins, and albuminuria. The main exposure, vigorous-intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The largest study ( n = 588) relied on surveys delivered during clinic visits and found that adolescents with T2D who report being active on three or more days per week display lower HbA1c levels and higher high density lipoprotein cholesterol, compared to less active adolescents 77 . A recent observational study from Canada found that that physically active adolescents with T2D were 40% less likely to have albuminuria (aOR: 0.60; 95% CI: 0.19, 0.84) and 50% less likely to have HbA1clevels above 8.0% (>60 mmol/mol; aOR: 0.50; 95% CI: 0.26, 0.98) 17 . Adolescents with T2D who engaged in regular vigorous intensity activity also observed a trend towards lower odds of nocturnal hypertension (aOR: 0.54; 95% CI: 0.27, 1.07).…”
Section: Type 2 Diabetes and Exercisementioning
confidence: 99%
See 3 more Smart Citations
“…The largest study ( n = 588) relied on surveys delivered during clinic visits and found that adolescents with T2D who report being active on three or more days per week display lower HbA1c levels and higher high density lipoprotein cholesterol, compared to less active adolescents 77 . A recent observational study from Canada found that that physically active adolescents with T2D were 40% less likely to have albuminuria (aOR: 0.60; 95% CI: 0.19, 0.84) and 50% less likely to have HbA1clevels above 8.0% (>60 mmol/mol; aOR: 0.50; 95% CI: 0.26, 0.98) 17 . Adolescents with T2D who engaged in regular vigorous intensity activity also observed a trend towards lower odds of nocturnal hypertension (aOR: 0.54; 95% CI: 0.27, 1.07).…”
Section: Type 2 Diabetes and Exercisementioning
confidence: 99%
“…76 For youth with T2D, there is little evidence for the influence of duration, type, or intensity of exercise on acute glycemic excursions or glucose time-in-range. Cross-sectional studies suggest that more frequent bouts of structured PA, 77 particularly vigorous intensity structured activity 17 are associated with improved glycemia and cardiometabolic risk factors.…”
Section: Reasons For Dysglycemia During Exercise In Youth With T1dmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 6 ] Persistent hyperglycemia will damage different organs and systems of the body. [ 7 ] For example, the incidence of lower limb amputation, myocardial infarction, visual impairment, and renal failure in patients with diabetes is higher than that in normal people. Physical dysfunction, decreased physical control ability, falls, urinary incontinence, pain, depression, and dementia are also very common among the elderly with diabetes.…”
Section: Introductionmentioning
confidence: 99%